On PLC Channel Emulation via Transmission Line Theory - Gruber, Florian; Lampe, Lutz (Proceedings of 2015 IEEE International Symposium on Power Line Communications and Its Applications (ISPLC), 2015)
The emulation of power line communication (PLC) channels is an important tool for the analysis and development of PLC systems. Especially for the study of PLC networks, the so-called bottom-up channel emulation using transmission-line theory (TLT) is the proper method. The underlying assumption of this approach is that the power line propagation characteristics are known. That is, the per-unit length (PUL) parameters of the power lines need to be computed. However, especially for multi-conductor lines this can be theoretically and computationally challenging. In this paper, we present a compact overview of the computation of PUL parameters. We briefly discuss the assumptions associated with different solution methods and develop a numerical solver applicable to general multi-conductor transmission lines. Considering a sample set of different cable types, we demonstrate the effects of simplifying assumptions on the accuracy of computed PUL parameters and channel frequency response
Keywords: carrier transmission on power lines; electromagnetic wave propagation; frequency response; multiconductor transmission lines; telecommunication channels; transmission line theory; PLC channel emulation; power line communication channel emulation; transmission line theory; PLC networks; TLT; bottom-up channel emulation; power line propagation characteristics; per-unit length parameter computation; general multiconductor transmission lines; numerical solver; channel frequency response computation; Conductors; Cable shielding; Cable insulation; Capacitance; Permittivity; Closed-form solutions